2000
DOI: 10.1001/archinte.160.7.1001
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Methicillin Resistance and the Effect of Inadequate Empiric Therapy on Survival in Patients With Staphylococcus aureus Bacteremia

Abstract: The results of this study support the safety of the restriction of vancomycin use in patients with clinically significant S aureus bacteremia. However, patients with a history of MRSA are more likely to have future MRSA infections and should receive empiric therapy using vancomycin for possible S aureus infections, particularly for nosocomial infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
54
2

Year Published

2001
2001
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(59 citation statements)
references
References 16 publications
3
54
2
Order By: Relevance
“…While this may translate into improved clinical outcomes, especially in those in whom MRSA is undetected and who have been treated empirically with a beta-lactam antibiotic, small studies have failed to demonstrate the benefit of early appropriate therapy (1,18).…”
Section: Discussionmentioning
confidence: 99%
“…While this may translate into improved clinical outcomes, especially in those in whom MRSA is undetected and who have been treated empirically with a beta-lactam antibiotic, small studies have failed to demonstrate the benefit of early appropriate therapy (1,18).…”
Section: Discussionmentioning
confidence: 99%
“…9 It is therefore necessary to make informed decisions regarding selection of empirical antibiotics. [10][11][12][13] Consideration of a patient's previous colonization status is important, because colonization predates most hospital and community-acquired infections. 10,14 Universal or targeted surveillance for MRSA has been implemented widely as a means of limiting transmission of this antibiotic-resistant pathogen.…”
mentioning
confidence: 99%
“…[10][11][12][13] Consideration of a patient's previous colonization status is important, because colonization predates most hospital and community-acquired infections. 10,14 Universal or targeted surveillance for MRSA has been implemented widely as a means of limiting transmission of this antibiotic-resistant pathogen. 15,16 Although results of MRSA screening are not intended to guide empirical treatment, they may offer an additional benefit among patients in whom clinical infection with S. aureus develops.…”
mentioning
confidence: 99%
“…Early and appropriate treatment of septicemia has been associated with a reduction in the rate of mortality (1, 9, 11). However, one study reported that although patients with MRSA bacteremia were less likely to receive effective antibiotic therapy, this was not significantly linked to an increased rate of mortality (22).…”
mentioning
confidence: 99%